2001
DOI: 10.1614/0890-037x(2001)015[0107:smcwmo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

S-Metolachlor Compared with Metolachlor on Yellow Nutsedge (Cyperus esculentus) and Peanut (Arachis hypogaea)1

Abstract: S-metolachlor was compared with metolachlor at four field locations in Texas during the 1996 and 1997 growing seasons in terms of yellow nutsedge control, peanut injury, and peanut yield. S-metolachlor caused peanut injury comparable to metolachlor when either herbicide was applied preplant incorporated or preemergence. Yellow nutsedge control was similar and peanut yields were comparable with the two herbicides. At one location where yellow nutsedge failed to develop, the untreated check produced one of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 17 publications
(39 reference statements)
3
22
0
1
Order By: Relevance
“…Peanut stunting with metolachlor has been noted in other studies [20,21,38,53]. In Georgia, early-season peanut growth suppression was related to metolachlor rate [20].…”
Section: Peanut Stuntsupporting
confidence: 53%
“…Peanut stunting with metolachlor has been noted in other studies [20,21,38,53]. In Georgia, early-season peanut growth suppression was related to metolachlor rate [20].…”
Section: Peanut Stuntsupporting
confidence: 53%
“…Dimethenamid alone caused almost no peanut stunting, while flumioxazin plus dimethenamid resulted in 6% or less peanut stunt. Grichar et al (2001) reported variable peanut stunt with metolachlor PRE, where stunting ranged from 5% or less with metolachlor at 1.7 kg/ha to greater than 20% with metolachlor at 4.5 kg/ha.…”
Section: And 2000 Studiesmentioning
confidence: 99%
“…Other common K3 herbicides include acetochlor, alachlor, butachlor, dimethenamid-p, flufenacet, Smetolachlor, and propachlor (Senseman 2007). Smetolachlor is frequently used in peanut for the control of various weeds including yellow nutsedge (Cyperus esculentus L.) and Benghal dayflower (Commelina benghalensis L.) (Grichar et al 2001;Grichar et al 2008;Prostko et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Other common K3 herbicides include acetochlor, alachlor, butachlor, dimethenamid-p, flufenacet, Smetolachlor, and propachlor (Senseman 2007). Smetolachlor is frequently used in peanut for the control of various weeds including yellow nutsedge (Cyperus esculentus L.) and Benghal dayflower (Commelina benghalensis L.) (Grichar et al 2001;Grichar et al 2008;Prostko et al 2005).Little information about the tolerance of legume crops to pyroxasulfone has been published in the literature. Although pyroxasulfone was initially targeted for PRE weed control in corn, soybean has shown good tolerance The soil type at the Ponder Research Station was a Tifton sand with 96% sand, 2% silt, 2% clay, 1.2% organic matter, and pH 6.0.…”
mentioning
confidence: 99%